Photosensitive heterostructures CdTe-PbTe prepared by hot-wall technique - Movchan, S.; Sizov, F.; Tetyorkin, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Hot-wall technique has been used for preparation of CdTe-PbTe heterostructures. BaF₂ single crystals served as substrates. Electrical, photoelectric properties as well as noise spectra were investigated. Heterostructures exhibit photosensitivity up to room temperatures in the middle infrared (IR) region. In the heterostructures investigated at room temperature the 1/f noise is observed at frequencies much less compared to those ones observed in PbSe photoresistors (f = 3000 Hz) for the same IR region. Carrier transport mechanisms and band diagram of the heterostructures are briefly discussed.